Quantitative spectral analysis of the sdB star HD188112: A helium-core white dwarf progenitor - Latour, Marilyn; Heber, Ulrich; Irrgang, Andreas; Schaffenroth, Veronika; Geier, Stephan; Hillebrandt, W.; Roepke, F. K.; Taubenberger, S.; Kromer, Markus; Fink, M. (Astronomy & Astrophysics, 2016)
Context. HD 188112 is a bright (V = 10 : 2 mag) hot subdwarf B (sdB) star with a mass too low to ignite core helium burning and is therefore considered a pre-extremely low-mass (ELM) white dwarf (WD). ELM WDs (M less than or similar to 0.3 M-circle dot) are He-core objects produced by the evolution of compact binary systems.Aims. We present in this paper a detailed abundance analysis of HD188112 based on high-resolution Hubble Space Telescope (HST) near-and far-ultraviolet spectroscopy. We also constrain the mass of the star's companion.Methods. We use hybrid non-LTE model atmospheres to fit the observed spectral lines, and to derive the abundances of more than a dozen elements and the rotational broadening of metallic lines.Results. We confirm the previous binary system parameters by combining radial velocities measured in our UV spectra with the previously published values. The system has a period of 0.60658584 days and a WD companion with M >= 0.70 M-circle dot. By assuming a tidally locked rotation combined with the projected rotational velocity (v sin i = 7.9 +/- 0.3 km s(-1)), we constrain the companion mass to be between 0.9 and 1.3 M-circle dot. We further discuss the future evolution of the system as a potential progenitor of an underluminous type Ia supernova. We measure abundances for Mg, Al, Si, P, S, Ca, Ti, Cr, Mn, Fe, Ni, and Zn, and for the trans-iron elements Ga, Sn, and Pb. In addition, we derive upper limits for the C, N, O elements and find HD188112 to be strongly depleted in carbon. We find evidence of non-LTE e ff ects on the line strength of some ionic species such as Si II and Ni II. The metallic abundances indicate that the star is metal-poor, with an abundance pattern most likely produced by diffusion effects.
Keywords: stars: abundances; stars: atmospheres; stars: individual: HD 188112; subdwarfs; white dwarfs; binaries: general